Life Cycle Assessment of Decaffeinated Coffee Beans Production - Shofinita, Dian; Lestari, Dianika; Fiorine, Fiorine; Rochili, Andreana; Raksajati, Anggit; Achmadi, Amarthya (Journal of Engineering and Technological Sciences, 2025)
Life Cycle Assessment (LCA) analysis was conducted on the simulation of the production process of decaffeinated coffee beans using ethyl acetate (EA) and dichloromethane (DCM) solvents. The methods employed include the cradle-to-gate system, the ReCiPe 2016 midpoint method, and a hierarchic perspective on OpenLCA. The analysis used 320 kg of Robusta coffee beans per batch with the scope of analysis consisting of planting, postharvest, transportation, and decaffeination. The overall results of the hotspot analysis were human carcinogenic toxicity, marine ecotoxicity, global warming, freshwater ecotoxicity, and land use of 8 x 101  kg 1,4-dichlorobenzene eq, 1 x 101 kg 1,4-dichlorobenzene eq, 6 x 104 kg CO2 eq, 7 x 100 kg 1,4-dichlorobenzene eq, and 3 x 104 m2a crop eq for both EA and DCM. Comparison of the two solvents shows that the biggest environmental impacts were marine ecotoxicity, freshwater ecotoxicity, and human carcinogenic toxicity of 8.52 x 100 kg 1,4-dichlorobenzene eq, 5.44 x 100 kg 1,4-dichlorobenzene eq, 7.65 x 100 kg 1,4-dichlorobenzene eq for EA, and 8.52 x 100 kg 1,4-dichlorobenzene eq, 5.61 x 100 kg 1,4-dichlorobenzene eq, 8.03 x 100 kg 1,4-dichlorobenzene eq for DCM. Cultivation, extraction, and drying were the stages of considerable environmental impact. The application of agroforestry, reduction of inorganic and organic fertilizers, and the use of more environmentally friendly electricity sources serve as alternatives to reduce emissions.